TINJAUAN YURIDIS TERKAIT STATUS PEROLEHAN SUARA CALON ANGGOTA LEGISLATIF TERPILIH YANG MENINGGAL DUNIA (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 57 P/HUM/2019 - Sri Rahma Yanti; Emilda Firdaus; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The Elected Legislative Member Candidate who dies is essentially replaced by the owner of the next most votes. The provisions governing the matter are contained in Article 422 and Article 426 paragraphs (1) and (3) of Law Number 7 of 2017 concerning General Elections. The purpose of writing this thesis: First, to find out the legal considerations of the Supreme Court Number 57 P/Hum/2019 which states about the status of the votes acquired by the elected legislative candidates who died. second, to find out the legal perspective of the general election regarding the legal considerations of the Supreme Court Number 57 P/Hum/2019. The author conducts research using normative juridical methods or literature studies in order to obtain secondary data, namely by studying and analyzing comparatively descriptive laws and regulations with theories that have a relationship with the problems studied.From the results of this study, there are two main things that can be concluded: First, the legal considerations in the Supreme Court Decision Number 57 P/Hum/2019 contradict the contents of Article 422, Article 426 paragraphs (1) and (3) of Law Number 7 Year 2017 concerning General Elections. Second, Based on the Perspective of Election Law in Law Number 7 of 2017 concerning General Elections, it is stated that those who replace the elected Legislative Member candidates who die are based on the majority of votes.The author's suggestion is that the Supreme Court as one of the actors of judicial power in the case of the application for the right to judicial review is to pay more attention to the applicable laws and regulations in providing legal considerations. So that in the future the parties involved in the case, namely the applicant and the respondent, do not result in misunderstanding the decision or causing errors. Legislation under laws such as PKPU relating to the issues discussed above in order to pay more attention to laws and regulations that have a higher position, namely in this study Law Number 7 of 2017 concerning Elections. As well as paying attention to matters including the rights of election participants, namely political parties which have also been stated in Law Number 2 of 2008.Keywords: Juridical Review – Voting Status – Legislative Candidate